Modelling the impact of different permit allocation rules on optimal power plant portfolios - Christoph Weber; Philip Vogel; Oliver Woll (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2007)
The electricity generation mix of many European countries is strongly dominated by fossil fuelled power plants. Given that CO2-emissions are responsible for a major part of the anthropogenic greenhouse effect, emission trading has been introduced in the EU in 2005. Under the European emissions trading scheme (ETS), the emission quantities of major industry branches, most notably the electricity industry are capped and a system of tradable CO2 emission permits is established. Although the effects of emission trading on emissions, industry structure and investment had been analysed on beforehand by a number of models, the impact of rules for primary permit allocation has so far hardly been focused on. This was mostly seen as a distributional issue not affecting the efficiency of the market mechanism itself. However a closer look at the permit allocation rules shows that the number of permits allocated to new plants often depends on their fuel and technology (e. g. in Germany). This may consequently have distorting effects on market prices and investment decisions, which so far have been hardly investigated quantitatively. In order to analyse such effects, a mixed complimentary programming (MCP) model is developed, which allows to model investment incentives in the electricity sector. It takes into account major power generation technologies, emission constraints, endogenous investment allocation rules and price elasticity of demand. In particular also the time-varying structure of electricity demand is accounted for and the corresponding distinction of base- and peak-load technologies. The model is applied to the EU-27 focusing on the year 2015, i.e. on the third trading period, where so far no decision has been made on the allocation rules to be applied. From this analysis we derive the average market prices for emission allowances and electricity and the optimal power plant capacities under different allocation schemes. In a pure environmental perspective the auctioning of permits is expected to be a first-best solution, but it could endanger the competitiveness and the security of supply of the European Union. The reason for the latter is that the generation mix becomes biased in favour of gas fuelled plants, which are associated with the least specific CO2-emissions, but have to be imported to a large extent from politically unreliable regions like Russia or the Middle East. The results of our analysis however show that allocating emissions for free, based on expected full-load hours and fuel specifics, will lead to higher CO2-prices whilst the effect of securing supply is only limited. Also electricity prices will only be slightly lower, so that the contribution of free allocation schemes to economic competitiveness is also limited.
Keywords: P51; Q40; Q41; Q58; 330; climate protection; security of supply; emission trading; allocation of emission permits; electricity markets; power plant portfolio